Independent immigrants a settlement of Hanoverian Germans in western Missouri - Frizzell, Robert W., 1947- (University of Missouri Press, 2007)
"Frizzell examines the American immigrant experience of German peasant farmers from the Kingdom of Hanover, who immigrated to Lafayette County, Missouri, to form a new community centered on the town of Concordia, showing how it differed from other German immigrant communities in America and how it flourished after the Civil War"--Provided by publisher.